2020
DOI: 10.1371/journal.pone.0243437
|View full text |Cite
|
Sign up to set email alerts
|

The side effect profile of Clozapine in real world data of three large mental health hospitals

Abstract: Objective Mining the data contained within Electronic Health Records (EHRs) can potentially generate a greater understanding of medication effects in the real world, complementing what we know from Randomised control trials (RCTs). We Propose a text mining approach to detect adverse events and medication episodes from the clinical text to enhance our understanding of adverse effects related to Clozapine, the most effective antipsychotic drug for the management of treatment-resistant schizophrenia, but underuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 64 publications
0
27
0
2
Order By: Relevance
“…Women are more likely to develop hyperglycaemia and diabetes and increases in weight and body mass index[ 122 , 126 ]. There is very little evidence of gender differences in other side effects, though certain studies have found haematological abnormalities and constipation to be commoner among women[ 122 , 125 , 128 , 129 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are more likely to develop hyperglycaemia and diabetes and increases in weight and body mass index[ 122 , 126 ]. There is very little evidence of gender differences in other side effects, though certain studies have found haematological abnormalities and constipation to be commoner among women[ 122 , 125 , 128 , 129 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…Therefore, Asian patients need lower doses at the start of treatment and slower upward titration to reach their optimum dose. Despite these pharmacokinetic dissimilarities, ethnic differences seem to have minimal impact on the prevalence of adverse effects of clozapine[ 129 ]. Nevertheless, non-White ethnicity is a risk factor for metabolic syndrome, and certain studies have found a higher prevalence of hypertension and weight gain in Asians[ 127 , 136 ].…”
Section: Preventing Resistance To Clozapine Treatmentmentioning
confidence: 99%
“…In this sense, the use of clozapine, an atypical antipsychotic medication indicated for treatment-refractory schizophrenia 9 has been associated to an increased susceptibility to COVID-19 infection compared with other antipsychotic medications. 10 Moreover, prescribing clozapine requires close monitoring for serious adverse events, including agranulocytosis, myocarditis, aspiration pneumonia, and clozapine toxicity, as seizures, ileus and delirium, 11 , 12 which could be higher in the setting of COVID-19, as clozapine plasma concentrations increase during acute systemic infection because of the CYP1A2 enzymes’ inhibition by cytokines, 13 and the reduction or ceasing tobacco smoking in patients during acute illness. 14 …”
Section: Research Lettermentioning
confidence: 99%
“…Moreover, clozapine has more favorable efficacy on negative and depressive symptoms than paliperidone (Huhn et al, 2019). However, clozapine has several undesirable side effects, including over sedation, constipation, dizziness, hypersalivation, weight gain, tachycardia, headache, and constipation (Iqbal et al, 2020; Siskind et al, 2016). Metabolic syndrome has also been reported to be an undesirable adverse effect in patients taking clozapine (Wirshing et al, 1998), as it can lead to multiple systemic diseases.…”
mentioning
confidence: 99%